2013
DOI: 10.1111/codi.12439
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of tumour regression grade following neoadjuvant chemoradiation therapy for rectal cancer

Abstract: Our findings support the notion that ypCR status, nodal status after neoadjuvant CRT and CRM status, but not TRG, are predictors of long-term survival in patients with locally advanced rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…In these data sets, the use of ACEIs/ARBs did not significantly affect LR‐free survival, metastasis‐free survival, or OS. Prior studies have consistently identified a positive association between pCR and improved rates of locoregional disease control and OS . However, in these databases from UW and UH, the association of pCR with LR and OS rates did not reach significance.…”
Section: Discussionmentioning
confidence: 68%
“…In these data sets, the use of ACEIs/ARBs did not significantly affect LR‐free survival, metastasis‐free survival, or OS. Prior studies have consistently identified a positive association between pCR and improved rates of locoregional disease control and OS . However, in these databases from UW and UH, the association of pCR with LR and OS rates did not reach significance.…”
Section: Discussionmentioning
confidence: 68%
“…Prognostic markers such as ypN, LVI and PNI are commonly used to assess patient's risk of recurrence and therefore negate recommendation for adjuvant chemotherapy. However inconsistent reports on the significance of these markers to predict patient's prognosis is a concern . By comparing the pooled HR results for each covariate, no response has the highest HR of 2.97, compared with the LVI HR of 1.4, the ypN HR of 2.2 and the PNI HR of 2.3.…”
Section: Discussionmentioning
confidence: 99%
“…The American Joint Committee on Cancer/College of American Pathologists (AJCC/CAP) recommended in 2010 to use a three tiered-system that considers the relative proportion of fibrosis and viable tumor cells, as proposed by Ryan et al (4,5). Many authors have analyzed the prognostic significance of the different pathologic response grading systems with varying results (6,7), but very few studies have compared the different response patterns found in the tumor. The aim of this study is to analyze the pathologic response in our series of 183 patients from two Spanish hospitals and to determine whether there are different patterns of response and their prognostic significance.…”
Section: Original Articlementioning
confidence: 99%